Socialization of Making Liquid Organic Fertilizer from Mango Leaves and Palm Sugar to Improve Community Knowledge and Skills - Mardiah, Faijah; Rijal, Muhammad; Astuti, Lidya; Rosmiani, Ni Nengah; Sahputri, Masri Yanti; Tri Yunarni, Baiq Reinalda (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2024)
The agricultural sector is a key element in Indonesia's economic development, but the excessive use of chemical fertilizers has led to a decrease in soil fertility and an increase in production costs. This research aims to improve the knowledge and skills of the people of Bentek Village through socialization of the manufacture of liquid organic fertilizer (LOF) made from mango leaves and palm sugar as an environmentally friendly solution. The research method used is a qualitative descriptive approach with a case study of socialization of LOF making in Bentek Village, Gangga District, North Lombok Regency. The results of the study show that the application of liquid organic fertilizer is able to increase agricultural productivity with rice yields increasing by 12% and vegetables by up to 15%, as well as reducing production costs by up to 25%. In addition, the use of LOF improves soil quality with the addition of organic matter by 10-15% and water retention by up to 18%, which contributes to the sustainability of agriculture in the village. This socialization program not only has a positive impact on farmers, but also increases the interest of the younger generation to be involved in environmentally friendly agriculture. The socialization of liquid organic fertilizer technology has succeeded in providing significant economic and environmental benefits, reducing dependence on chemical fertilizers, and strengthening the economic resilience of the community. Ongoing support from the government and related institutions is urgently needed to ensure the sustainability of this program and expand its implementation.